2015
DOI: 10.1142/s0219633615500236
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of free energy changes due to mutations from alchemical free energy simulations

Abstract: How a mutation a®ects the binding free energy of a ligand is a fundamental problem in molecular biology/biochemistry with many applications in pharmacology and biotechnology, e.g. design of drugs and enzymes. Free energy change due to a mutation can be determined most accurately by performing alchemical free energy calculations in molecular dynamics (MD) simulations. Here we discuss the necessary conditions for success of free energy calculations using toxin peptides that bind to ion channels as examples. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…A stable binding mode for the GMT is necessary for accurate FEP predictions as shown in previous studies [ 25 , 28 ]. We examined the pose stability of ten ProTx-II mutants for three different kinds of FEP simulations: no membrane present, membrane present, and Cɑ position restraints present.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A stable binding mode for the GMT is necessary for accurate FEP predictions as shown in previous studies [ 25 , 28 ]. We examined the pose stability of ten ProTx-II mutants for three different kinds of FEP simulations: no membrane present, membrane present, and Cɑ position restraints present.…”
Section: Resultsmentioning
confidence: 99%
“…FEP performed well for charge-change mutations with an RMSE of 0.96 ± 0.15 kcal/mol and an R 2 of 0.81. This category of mutations has historically been challenging for FEP [ 28 ], suggesting that recent improvements for predicting charge-changes [ 25 ] were effective. Taken together, these data suggest that FEP can be used to accurately predict how a mutation to a GMT that targets VSDII of Nav1.7 will affect its potency for the channel, setting the stage for its prospective application in biologics drug discovery programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the ΔΔG b for the F23A mutant was calculated to be ~9.8 kJ/mol, in good agreement with the experimental value of ~7.8 kJ/mol. Similarly, another simulation study showed that the mutation R29A in the peptide ShK, a potent inhibitor of Kv1.1, changes the peptide’s binding mode, which prevented the use of FEP to calculate ΔΔG b [ 98 ]. In fact, mutations of charged residues pose a particular challenge for FEP calculations.…”
Section: Simulation Studies Of Peptide-channel Complexesmentioning
confidence: 99%
“…In fact, mutations of charged residues pose a particular challenge for FEP calculations. To address this issue, Rashid et al [ 98 ] reported a multi-step approach in which the Lennard-Jones interactions are decoupled from the Coulomb interactions and the mutation is simultaneously performed on the residue in the bound and unbound state. The approach was used to calculate the ΔΔG b for the R18A mutation in the peptide-channel complex HsTx1-K V 1.1 and the data showed good agreement with experiments.…”
Section: Simulation Studies Of Peptide-channel Complexesmentioning
confidence: 99%